Strategy, Organization and the Changing Nature of Work - Wood, Geoffrey (Relations Industrielles / Industrial Relations, 2003)
Reviews the book "Strategy, Organization and the Changing Nature of Work," edited by Jordi Gual and Joan E. Ricart.
Keywords: BOOKS -- Reviews; BUSINESS planning; Nonfiction; STRATEGY, Organization & the Changing Nature of Work (Book)